Adapt or fall - the coffee experience - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A report from northern Tanzania featuring staff of a coffee estate and smallholder farmers, who describe how they are either succeeding or failing to cope with reduced rainfall.